Part 2 Composition Materials With Metal Matrix Condensed from the Vapor Phase (Journal of Material Science and Technology Research, 2021)
In this article, the present-day problems of microporous condensed materials obtained from the vapor phase are discussed. The pore sizes are regulated by the amount of the second phase concentration and the deposition temperature.The oxides, fluorides, and sulfides can be used as the second phase and non-removable inclusions. The open porosity can be regulated from 0% to 50 %of the porosity and with average porose sizes of 0.1 to 8 µm. The condensed micro-porous materials can be deposited in coating form or the form of massive bulk sheet materials with a thickness of up to 6 mm and a diameter of 1m.